THE USE OF CODE-MIXING BY THE MEMBERS OF GROUP KELUARGA FAKULTAS SASTRA - Setyawati, Amdini Pratama; Novitasari, Nine Febrie; Lailiyah, Sufil (Universitas Negeri Malang, 2023)
Because of the advanced development of technology, people can now interact with others easily by any means of communication, such as text messages and telephone calls. One of the most popular applications that has messaging and call features is WhatsApp. WhatsApp messaging feature is also used by the lecturers, students, and staff of English Department at Universitas Abdurachman Saleh Situbondo for sharing both academic and non-academic information. The group members communicate using Indonesian, English, and the mix of the two. This current research analyzed the types of code mixing used by the members of the group and the reasons why they used code mixing. The data of this descriptive qualitative research are the utterances containing code mixing made by the members of the group. Muysken’s theory was used to analyze the types of code mixing and Bhatia’s was used to study the reasons for using code mixing. The result of this research shows that insertion is the onl type of code mixing which appeared in the group, while situational factor is the most used reason why the code mixing occurred.